RESEARCH IS A DAILY ACTIVITY AN UNDERSTANDING NEEDED TO ATTRACT THE ATTENTION OF PROSPECTIVE RESEARCHERS - Larasdiputra, Gde Deny (TEMA, 2023)
Problems are something that will always arise in life. A problem solver is certainly the most sought after when a complex problem occurs, the cause is found, and even how to solve it. In situations like this, "research" activities are needed to train an individual's skills. But sometimes for most students in their undergraduate studies, research is considered very difficult but must be passed to get their education degree. Sometimes scientific language that is difficult to understand makes it appear that it requires a high IQ. Collecting data in this study using unstructured interviews which are free interviews where researchers do not use interview guidelines that have been arranged systematically and completely for data collection. Researchers discussed with students the concept of a multimodal method that can help see the problem from a visual, auditory perspective or can be shaped like a story, maybe it can increase the enthusiasm of young researchers. Making the concept of storytelling, having fun, and realizing that this skill is needed for everyday life is needed. Think of it as being a researcher like a detective isn't it fun?